Tuning the Liquid Crystallinity of Cholesteryl-o-Carborane Dyads: Synthesis, Structure, Photoluminescence, and Mesomorphic Properties - Albert Ferrer-Ugalde; Arántzazu González-Campo; José Giner Planas; Clara Viñas; Francesc Teixidor; Isabel M. Sáez; Rosario Núñez (Crystals, 2021)
A set of mesomorphic materials in which the o-carborane cluster is covalently bonded to a cholesteryl benzoate moiety (mesogen group) through a suitably designed linker is described. The olefin cross-metathesis between appropriately functionalized styrenyl-o-carborane derivatives and a terminal alkenyl cholesteryl benzoate mesogen (all type I terminal olefins) leads to the desired trans-regioisomer, which is the best-suited configuration to obtain mesomorphic properties in the final materials. The introduction of different substituents (R = H (M2), Me (M3), or Ph (M4)) to one of the carbon atoms of the o-carborane cluster (Ccluster) enables the tailoring of liquid crystalline properties. Compounds M2 and M3 show the chiral nematic (N*) phase, whereas M4 do not show liquid crystal behavior. Weaker intermolecular interactions in the solid M3 with respect to those in M2 may allow the liquid crystallinity in M3 to be expressed as enantiotropic behavior, whereas breaking the stronger intermolecular interaction in the solid state of M2 leads directly to the isotropic state, resulting in monotropic behavior. Remarkably, M3 also displays the blue phase, which was observed neither in the chiral nematic precursor nor in the styrenyl-cholesterol model (M5) without an o-carborane cluster, which suggests that the presence of the cluster plays a role in stabilizing this highly twisted chiral phase. In the carborane-containing mesogens (M2 and M3), the o-carborane cluster can be incorporated without destroying the helical organization of the mesophase.